APLIKASI PENDUKUNG KEPUTUSAN PENENTUAN PROMOSI JABATAN MENGGUNAKAN METODE PROFILE MATCHING (STUDI KASUS DI PT. PETROKIMIA GRESIK) - Wimpi Sancaka (Universitas Muhammadiyah Gresik, 2019)
Human resources play an essential role in helping companies to achieve their vision and mission. As a large scale company, PT Petrokimia Gresik obviously needs to invest in Employees’ Performance Assessment System. It could act as a decision-making tool or a measure to evaluate and assess employees' performance at work so that theemployees’ promotion would be moreobjective and organized. Decision support system could be used to reduce the subjectivity in decision-making process. The decision support system that uses profile matching method or competency gap analysis was created based on the data which refers to the decree of the board of directors issued by PT Petrokimia Gresik. This system analyzes and assesses employee’s competencies by grouping and calculating core factors and secondary factors in each variable. The output of the calculation is a ranking of the candidates. By implementing decision support system which uses Profile Matching method, it assists company decision-making process in promotion decision based on employees’ competency scores more optimally.